Actitudes hacia la Histerectomía Obstétrica en pacientes Atendidas en el servicio de Gineco - obstetricia del Hospital Minsa II-2 Tarapoto, Enero 2007 - Diciembre 2014 - Reyna Alva, Sharon Patricia (2016)
This research entitled "Attitudes towards obstetric hysterectomy in patients seen in the service of gynecology - obstetrics MOH II-2 Hospital Tarapoto, January 2007 - December 2014" not experimental, quantitative, basic, descriptive, retrospective prospective study, whose sample was 85 patients with obstetric hysterectomy, the methodology was reviewing medical records and interviews, the survey instrument. The results were: The sociodemographic characteristics predominate in patients with obstetric hysterectomy are: 32.9% (28) are 20-30 years old; 34.1% (29) having from 3 to more children. 50.6% (43) are cohabiting; 42.4% (36) have secondary education; 44.7% (38) are respectively rural and urban area. 45.9% (39) workers are occupying the home. The kind of attitude towards obstetric hysterectomy is favorable with 71.8% (61). The kind of attitude as most relevant dimensions to obstetric hysterectomy is: In the cognitive attitude is positive with 89.4% (76). In the affective it is indifferent to 52.9% (45). Conativo about what is indifferent 54.1% (46). Conclusion: Patients treated in the service of gynecology - obstetrics MOH II-2 Hospital Tarapoto, January 2007 - December 2014, have a favorable attitude in its cognitive dimension.